Early onset atrial lesions in a patient with a novel LMNA frameshift mutation. Issue 23 (8th July 2021) - Lin, Yongping; Liu, Hailei; Cui, Chang; Lin, Zhiqiao; Zhang, Yike; Zhu, Yue; Ju, Weizhu; Chen, Minglong
Abstract: Genetic mutations in the lamin A/C gene ( LMNA ) have been linked to cardiomyopathy. Different mutational sites exhibit different clinical manifestations and prognoses. Herein, we identified a novel LMNA frameshift mutation, p.P485Tfs * 67, from a patient with early-onset atrial disease. To verify the pathogenicity of this variation, a transgenic zebrafish model was constructed, which demonstrated that adult zebrafish with the LMNA mutation showed an abnormal ECG and impaired myocardial structure. Our study suggests the atrial pathogenicity of the LMNA -P485Tfs mutation, which is helpful to understand the function of the Ig-like domain of lamin A/C.